Language for the school going deaf children - K, Mohamed Fazlulla (Journal of All India Institute of Speech and Hearing)
In many states of the country the students have to study three languages in their school curriculum. The languages became a great barrier for the deaf children who try to be integrated in the schools for the normals. The problem gains in perspective when we remember that Language is the biggest problem for the deaf child.